2022
DOI: 10.1021/acsapm.2c01990
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Molecular Lock: A Universal Strategy for Hydrogel Adhesion

Abstract: Hydrogel adhesion is fundamental to a large number of established and emerging fields. The existing adhesion methods have some problems, such as the limited penetration ability of polymers in hydrogels, the interface hardening caused by in situ monomer polymerization, the secondary damage caused by covalent strong bonding during detachment, the need for complementary techniques to induce adhesion, and the complex and impractical operation. Inspired by the adhesion mechanism of mussels, we propose a universal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The described system is obtained via a simple one-step preparation without any risk of delamination, as the preparation does not involve the bilayer systems, as described in the literature. 43,44 For instance, Kirillova et al reported self-folding alginate films through a direct ink writing printing process creating a bilayer system. 45 They also obtained self-folding films with modified hyaluronic acid where the actuating mechanism is more related to the hydrogel film preparation process than to the exploitation of the cross-linking chemistry.…”
Section: Photo-cross-linking Of Methacrylated Alginatementioning
confidence: 99%
“…The described system is obtained via a simple one-step preparation without any risk of delamination, as the preparation does not involve the bilayer systems, as described in the literature. 43,44 For instance, Kirillova et al reported self-folding alginate films through a direct ink writing printing process creating a bilayer system. 45 They also obtained self-folding films with modified hyaluronic acid where the actuating mechanism is more related to the hydrogel film preparation process than to the exploitation of the cross-linking chemistry.…”
Section: Photo-cross-linking Of Methacrylated Alginatementioning
confidence: 99%
“…Smaller molecules can also induce molecular interlocking at the hydrogel–tissue interface. Zhang et al discovered that introducing TA, which is a bulky polyphenol molecule, in between the hydrogel–tissue junction can significantly enhance their bonding strength [ 119 ] (Figure 6B). The adhesion mechanism is initiated by the bidirectional passive diffusion and penetration of TA into the hydrogel/tissue structures.…”
Section: Principles and Designs For Hydrogel–tissue Adhesionmentioning
confidence: 99%
“…Strong hydrogel adhesion was achieved through catechol chemistry and the dissipative matrix. 33 The MIJ hydrogel performed with high sensitivity (GF = 0.842) in detecting human motion. Fe 3 O 4 @ PDA can be served as thermal interface materials (TIMs) and affect the thermal conductivity of the MIJ hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…The MIJ hydrogel was prepared by the cross-linking polymerization of acrylamide with alginate-calcium along with polydopamine-decorated Fe 3 O 4 nanoparticles (Fe 3 O 4 @PDA) at one side induced by a magnetic field to avoid uncontrollable material diffusion. Strong hydrogel adhesion was achieved through catechol chemistry and the dissipative matrix . The MIJ hydrogel performed with high sensitivity (GF = 0.842) in detecting human motion.…”
Section: Introductionmentioning
confidence: 99%